2016
DOI: 10.1111/jgs.14101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prevalence and Predictors of Frailty in Individuals with Human Immunodeficiency Virus

Abstract: HIV appears to be an independent risk factor for frailty, with frailty occurring in individuals with HIV at rates comparable with older individuals without HIV. Heterogeneity in study populations and frailty assessment measures hamper accurate description of the problem. Future longitudinal work with standardized methodology is needed to describe prevalence accurately and confirm predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 35 publications
12
70
1
1
Order By: Relevance
“…As a recent review suggested, these findings suggest that the microbiota and microbiome may influence the development or changes of the host immune system, contribute to inflamm‐aging, lead to certain chronic health conditions, and affect the aging process . Some studies suggest that certain viruses may be a risk factor for or predictor of frailty in older adults . Conversely, frailty and functional status have not only been associated with greater risk of infection, but also affect the outcomes of older adults with serious infections, especially respiratory infections …”
Section: General Problem Of Geriatric Infectious Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As a recent review suggested, these findings suggest that the microbiota and microbiome may influence the development or changes of the host immune system, contribute to inflamm‐aging, lead to certain chronic health conditions, and affect the aging process . Some studies suggest that certain viruses may be a risk factor for or predictor of frailty in older adults . Conversely, frailty and functional status have not only been associated with greater risk of infection, but also affect the outcomes of older adults with serious infections, especially respiratory infections …”
Section: General Problem Of Geriatric Infectious Diseasementioning
confidence: 99%
“…3 Some studies suggest that certain viruses may be a risk factor for or predictor of frailty in older adults. 5,6 Conversely, frailty and functional status have not only been associated with greater risk of infection, but also affect the outcomes of older adults with serious infections, especially respiratory infections. 7…”
Section: General Problem Of Geriatric Infectious Disease Epidemiologymentioning
confidence: 99%
“…Frailty is a phenotype that accounts for some of this variability; within each stratum of disability, frailty predicts survival [1,2]. Adults living with HIV exhibit frailty more frequently than HIV-negative individuals of similar age, but whether this increase is a consequence of HIV itself or of its comorbidities is debated [3,4]. Some also question the validity of frailty measurement tools in populations with mean ages under 50 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Adults living with HIV exhibit frailty more frequently than HIV-negative individuals of similar age, but whether this increase is a consequence of HIV itself or of its comorbidities is debated [3,4]. Some also question the validity of frailty measurement tools in populations with mean ages under 50 [3,4]. As combination antiretroviral therapy (cART)-era HIV populations enter decades for which common frailty measures were designed, determinants of frailty will be important to identify in order to optimize clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline frailty status predicted adverse patient outcomes such as falls, hospitalisation and death 4. This model is the most frequently used tool in frailty research,6 especially in the context of HIV 7. However, it has been challenged as being less practical to apply in clinical settings and criticised for its unidimensional nature that focuses mainly on muscle strength and function, neglecting psychological and social factors which are known to impact on frailty 3 8…”
mentioning
confidence: 99%